Lack of Association of Childhood Partial Epilepsy with Brain Derived Neurotrophic Factor Gene - Aycan Unalp; Elcin Bora; Tufan Cankaya; Ozlem Giray Bozkaya; Derya Ercal; Aysel Ozturk; Ayfer Ulgenalp (The Scientific World Journal)
Brain-derived factor (BDNF) is a member of neurotrophin family and is localized and upregulated in areas implicated in epileptogenesis. Several lines of evidence make the BDNF gene a plausible candidate gene for predisposition to epilepsy. In this study, we tested that BDNF might be involved in the etiology of childhood PE. To assess whether BDNF gene C270T polimorphism could be implicated in vulnerability to PE, we conducted a case-control association analysis (112 partial epileptic and 100 controls) in Turkish children. Epileptic children were divided into two groups: 1—idiopathic (n=85) and 2—symptomathic epilepsy (n=27). There was no significant difference in genotypic distribution and allelic frequencies of the BDNF gene C270T polimorphism between the PE and control groups. However, the BDNF gene TT genotype was more frequently seen in the epileptic children (15 versus 11 patients, resp.). Interestingly, in the epilepsy group, both two children with TT genotype have posttraumatic epilepsy. The data indicate a possible association with the 270T genotype of the BDNF gene with a posttraumatic epilepsy. To draw any conclusion, further studies using larger sample sizes should be carried out in various ethnic populations in childhood epilepsies.